High-Speed Rail - Yaghoubi, Hamid (IntechOpen, 2019)
The rapid expansion of transportation industries worldwide, including railways, and the never-ending desire to reduce travel time have highlighted the need to resort to advanced transit systems. Conventional railway systems have been modified to make them travel at much higher speeds. High-Speed Rail includes the main topics and basic principles of high-speed railways (HSRs). The book reflects new engineering and track developments, the most current design methods, as well as the latest industry standards and policies. It provides a comprehensive overview of the significant characteristics for HSRs; highlights recent advancements, requirements, and improvements; and details the latest techniques in the global market. High-Speed Rail contains a collection of the latest research developments on HSRs. This book comprehensively covers basic theory and practice in sufficient depth to provide a solid grounding for railway engineers. It also helps readers maximize effectiveness in all facets of HSRs. This professional book as a credible source and a valuable reference can be very applicable and useful for professors, researchers, engineers, practicing professionals, trainee practitioners, students, and others interested in HSRs.